2022
DOI: 10.3389/fpubh.2022.889973
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SARS-CoV-2 Mutations on PCR Assay Sequence Alignment

Abstract: Real-time reverse transcription polymerase chain reaction (RT-PCR) assays are the most widely used molecular tests for the detection of SARS-CoV-2 and diagnosis of COVID-19 in clinical samples. PCR assays target unique genomic RNA regions to identify SARS-CoV-2 with high sensitivity and specificity. In general, assay development incorporates the whole genome sequences available at design time to be inclusive of all target species and exclusive of near neighbors. However, rapid accumulation of mutations in vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…As demonstrated in previous studies, clade-specific detection and resistance to false negatives due to primer sequence drift are critical to understanding the dimensions of an outbreak and coordinating a robust and effective public health response (26). The combination of algorithms in BioLaboro creates specific primer candidates and reliably assesses their performance in silico prior to in vitro testing which significantly contributes to a rapid diagnostic and public health response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As demonstrated in previous studies, clade-specific detection and resistance to false negatives due to primer sequence drift are critical to understanding the dimensions of an outbreak and coordinating a robust and effective public health response (26). The combination of algorithms in BioLaboro creates specific primer candidates and reliably assesses their performance in silico prior to in vitro testing which significantly contributes to a rapid diagnostic and public health response.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work using the BioLaboro pipeline focused primarily on the PSET component to track predicted PCR assay performance over time and debug associated design issues. For example, a previous SARS-CoV-2 study demonstrated the sudden increase in failure rate of several assays related to deletions in the S gene as the virus evolved (26). This motivated the development of a new feature for PSET, which was the inclusion of 5'/3'-sequence context in the primer sequence query to increase local alignment quality and detect additional, potentially deleterious mutations outside of the binding target.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR Signature Erosion Tool (PSET) provides an in silico method for determining primer binding sites relative to taxonomically related sequences and detects mutations in primers used for PCR or qPCR assays (20,21). For this study, we created LAMP assays for V. cholerae detection, beginning with improvements to PSET, and culminating with a robust, quantitative determination of the assay outcome using computer vision.…”
Section: Introductionmentioning
confidence: 99%
“…The new LAMP workflow module for PSET can generate assays or predict performance with respect to large reference sequence databases, such as the NCBI nucleotide (nt) database. Running the tool periodically can identify potential assay failures as newly evolved sequences are deposited into databases such as GenBank or GISAID (20). Additionally, we developed a LAMP assay design tool based on the open source Primer3 program as an alternative to web-based programs, leveraging multicore architecture.…”
Section: Introductionmentioning
confidence: 99%